2009
DOI: 10.1111/j.1750-3841.2009.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Quality of Hibiscus (Hibiscus sabdariffa) for Developing the Natural‐Product Industry in Senegal

Abstract: The objectives of this study were to assess and improve the quality of the hibiscus calyces from Senegal over 2 production seasons (2004 to 2005), to develop and adapt new procedures for the determination of hibiscus anthocyanins and analysis of the 2 major ones, delphinidin-3-sambubioside and cyanidin-3-sambubioside. The foreign matter, total ashes, and acid insoluble ashes showed that the calyces harvested in 2005 were produced following hygienic practices, while the color assessment of the calyces and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
41
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 15 publications
13
41
0
5
Order By: Relevance
“…According to Juliani et al (2009), the total content of anthocyanins (by HPLC) in calyces of H. sabdariffa varies a The values represent means of triplicate measurements; b IC 50 = concentration for 50% inhibition of DPPH remaining. The means followed by same letter in column do not differ based on the Tukey test (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…According to Juliani et al (2009), the total content of anthocyanins (by HPLC) in calyces of H. sabdariffa varies a The values represent means of triplicate measurements; b IC 50 = concentration for 50% inhibition of DPPH remaining. The means followed by same letter in column do not differ based on the Tukey test (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Many edible plants are sources of anthocyanins (Mazza, 2000;Mertz, Cheynier, Gunata, & Brat, 2007;Prodanov, Dominguez, Blazquez, Salinas, & Alonso, 2005;Reyes & Cisneros-Zevallos, 2007), including the calyces of roselle (Hibiscus sabdariffa L.) Du & Francis, 1973;Wong, Yusof, Ghazali, & Che-Man, 2002). Several authors have confirmed that H. sabdariffa is a good source of dietary antioxidants, with its calyces containing amounts of anthocyanins as high as 2.5 g 100 g − 1 DW (Aurelio, Edgardo, & NavarroGalindo, 2008;Juliani et al, 2009). The calyces contain two major anthocyanins: delphinidin 3-xylosylglucoside (also called delphinidin 3-sambubioside or hibiscin) and cyanidin 3-xylosylglucoside (also called cyanidin 3-sambubioside or gossypicyanin).…”
Section: Introductionmentioning
confidence: 94%
“…The red and burgundy calyces are used for obtaining aqueous extracts to prepare refreshing drinks; green calyces are used to prepare soups with vegetables (Babalola et al 2001). The economic interest of Roselle varieties lies in their dried calyces which are used worldwide in the production of beverages, jellies, sauces, liqueurs, wines, and preserves; it is also used as a source of natural dye for foods due to the presence of anthocyanins (Juliani et al 2009). The manufacturing of Roselle calyces based products and its extracts could be a promising alternative for the food and beverage industries.…”
Section: Introductionmentioning
confidence: 99%